PERBANDINGAN HASIL BELAJAR KELAS EKSPERIMEN DAN KELAS KONTROL PADA PENGGUNAAN PEMBELAJARAN METODE CERAMAH DENGAN MENGGUNAKAN QUIZ INTERAKTIF PADA MATA PELAJARAN PAI PADA KELAS I DI SDIT IZZATUL ISLAM KARAWANG - Fathin Ihsanul Haq; Sabrina Septiani; Rafiff Fendiansyah; Nandia Latifah (STKIP Subang, 2026)
This study aims to determince the comparison of student learning outcomes between the experimental class using the lecture methode assisted by interactive quizzes and the control class using the conventional lecture method ini Islamic Religious education (PAI) subjects for first grade student at SDIT Izzatul Islam Karawang. This research employed a quantitative approach with a quasi experimental design using a pree test posstest control group design. The research sample consisted of an experimental claas and a control class. Data collection’s techniques included tests, observations, and documention. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, Independent Sample t-Test, and N-Gain analysis with the assistances of SPSS Software. The findings showed that the average score of the experimental class increased from 65.31 to 84.69, while the control class increased from 66.67 to 73.33. the Independent Sample t-Test result indicated a signifance value of 0,000 < 0.05, demonstrating a significant difference between the two classes. Furthermore, the N-Gain score of the experimental class was 0,56 categorized as moderate, while the control class obtained 0,20, categorized as low. Therefore, the lecture method assisted by interactive quizzes proved to be more effective than the conventional lecture method in improving students learning outcomes in Islamic Religious Educations Subjects.